Too Blue To Be True”: Indoxacarb Induced Methemoglobinemia- A Rare Case - Jerry Jacob; Karthik Reddy C H; Jobin James; Nijila Janardhanan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Indoxacarb is an oxadiazine insecticide, which is a sodium channel blocker in the nervous system of insectsand causes mild tremors, cessation of feeding, and death in few hours.Here we describe a case of novaluron and indoxacarb poisoning in a suicide attempt. The patient presentedwith cyanosis with saturation – paO2 gapindicating methemoglobinemia and was treated with methyleneblue and other supportive measures.